Ion Transport in Chloroplast and Mitochondria Physiology in Green Organisms - Cornelia Spetea (Frontiers Research Topics, 2017)
Chloroplasts and mitochondria both have a prokaryotic origin, carry essential genes on their own highly reduced genome and generate energy in the form of ATP for the plant cell. The ion composition and concentration in these bioenergetic organelles impact photosynthesis, respiration and stress responses in plants. Early electrophysiological and biochemical studies provided strong evidence for the presence of ion channels and ion transporters in chloroplast and mitochondrial membranes. However, it wasn't until the last decade that the development of model organisms such as Arabidopsis thaliana and Chlamydomonas reinhardtii along with improved genetic tools to study cell physiolgy have led to the discovery of several genes encoding for ion transport proteins in chloroplasts and mitochondria. For the first time, these discoveries have enabled detailed studies on the essential physiological function of the organellar ion flux. This Research Topic welcomed updated overviews and comprehensive investigations on already identified and novel ion transport components involved in physiology of chloroplasts and mitochondria in green organisms.